The development dynamics of a small higher education system Iceland : a case in point - Gyða Jóhannsdóttir 1944-; Jón Torfi Jónasson 1947- (2013)
Carried out in 2011 to 2012, this study investigated how the higher education (HE) system has developed in a small country, Iceland, compared to the HE systems of larger countries, such as the US, Japan and other Nordic and European countries. Similarities and differences in the HE systems were sought by focussing on the fol-lowing issues: 1) the expansion of HE participation, 2) the structural development of HE systems and various categories of academic drift, and 3) the regulation and evaluation of HE institutions, including the establishment of quality assurance agencies. The article intends to answer three questions: 1. To what extent can it be assumed that HE develops in essentially the same way in a very small system as in larger or even much larger systems? 2. Does Icelandic HE present significantly different drivers of change than larger systems for which comparable data exist? 3. Can specific development problems be identified in a small system that do not come to the fore in the larger systems? Our data stem from the available literature as well as various official documents and statistical data banks. Regarding the dimensions explored, the principal conclusions are that small and large systems show essentially the same development characteristics. Governmental and institutional agents as well as students were also revealed to act in similar ways, whether in small or large systems. On the whole, Icelandic HE faces the same problems as larger systems, even though some differences were found, such as in Iceland students having had until recently to go abroad for graduate studies, and in the implementation of quality systems, as through quality assurance agencies. Í rannsókn frá árunum 2011−2012 er þróun háskólamenntunar í litlu landi, Íslandi, könnuð í ljósi af þróun háskólamenntunar í stærri löndum, einkum á Norðurlöndum en einnig í öðrum Evrópulöndum, Bandaríkjunum og Japan. Kannað er hvað er líkt og ólíkt með þróuninni á Íslandi og annars staðar og sjónum er beint að eftirfarandi þáttum: 1. Þenslu ...